FREQUENCY OF MODIFIABLE RISK FACTORS IN STROKE PATIENTS - Zuhaid, Muhammad; Salman, Salman; Chawla, Javed Akhtar; Farooq, Umer; Ahmad, Aamir; Khan, Saminullah; Asfandiyar, Momina (Journal of Ayub Medical College Abbottabad, 2014)
Background: Stroke is one of the common causes of admission in medical and neurology units in hospitals. The aim of this study was to find out the frequency of modifiable risk factors, and association of ischaemic stroke with these risk factors in stroke patients admitted in Ayub Teaching Hospital Abbottabad. Methods: This a cross-sectional descriptive hospital based study, carried out in medical units of Ayub Teaching Hospital, Abbottabad on 150 patients with stroke. Thorough history, clinical examination and appropriate investigations were performed to collect all the relevant information. CT scan was done to confirm the diagnosis. Results: Out of 150 subjects, 90 (60%) were males, while 60 (40%) were females. Ischaemic stroke was found in 105 (70%) patients and 45(30%) were having haemorrhagic stroke. The risk factors were hypertension in 127 (84.7%), diabetes 31 (20.7%), Coronary artery diseases 31 (20.7%), previous TIA/stroke 42 (28%), smoking 28 (16.7%) and obesity 16 (10.7%). Conclusion: There was no statistically significant association between risk factors and type of stroke except coronary artery diseases. Keywords: Modifiable risk factors, Stroke, Coronary artery disease